Determinan Perilaku Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita Di Puskesmas Bawomataluo Kecamatan Fanayama Kabupaten Nias Selatan Provinsi Sumatera Utara - Januariana, Neni Ekowati; Khairatunissa, Khairatunissa; Sari Siregar, Dian Maya; Asriwati, Asriwati; Sarumaha, Yermin (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Various kinds of diseases in children that need to be watched out and the most common diseases suffered by children is Acute Respiratory Infection (ARI). Based on data from the World Health Organization in 2019, lower respiratory tract infections reduced life expectancy by 2.09 years in sufferers. Based on the results of the South Nias Regency Central Statistics Agency (BPS) in 2019, ARI is one of the biggest diseases in South Nias Regency, namely 611 cases. This study aimed to determine the factors associated with the incidence of ARI in Bawomataluo Village, Fanayama District, South Nias Regency in 2022. This is analytic observational research using a cross-sectional approach that was conducted at Bawomataluo Village, Fanayama District, South Nias Regency. The sample was determined by Nonprobability Sampling with purposive sampling method the number of samples in this study were 72 respondents. lts of the chi-square test obtained on the exclusive breastfeeding variable p=0.000, immunization p=0.020, knowledge p=0.000, exposure to cigarette smoke p=0.000 which indicates the presence of associated factors. Conclusion of this study shows that there is a relationship between exclusive breastfeeding, immunization, knowledge and exposure to cigarette smoke with the incidence of ARI in toddlers at Bawomataluo Village, Fanayama District, South Nias Regency in 2022. It is suggested to the research site to be able to improve environmental cleanliness, especially reduce air pollution so that the number of ARI does not continue to increase and for parents of toddlers is expected to increase knowledge about ARI disease in order to better understand its prevention early.